Reideologi Warga Eks HTI: Doktrinisasi Nasionalisme, Moderasi Islam Dan Indonesia - Pasiska Pasiska; Zainal Azman (Sekolah Tinggi Agama Islam (STAI) Bumi Silampari, 2020)
In this paper, we will review the phenomena that are present in this nation: this phenomenon is none other than the existence of a movement that is able to hegemony the community for love for the homeland carried out by former HTI residents, the method used in the research is descriptive qualitative research about what happens in everyday life, either in social media and phenomena that exist in society. As for the form of Reidology with the character education approach, the character education in question combines the concept of Islamic education in Islamic schools and education in state defense whose output gives birth to the nation's children, especially former HTI residents to return to love the Republic of Indonesia. Why is this important to do, so that there are no longer Indonesian citizens who are in crisis of nationalism and play an active role in filling this independence from a development perspective in their own way.